Success in information technology - what do student nurses think it takes? A quantitative study based on Legitimation Code Theory - Mike Johnson (Association for Learning Technology, 2018)
The goal for learners to make successful use of information technology (IT) has become a staple of education policy and curriculum. The literature about how this can be achieved offers various conceptions of this goal, namely, skills, competence, literacy, fluency, capabilities, etc. When these concepts are reified as a taxonomy or model, they are presented in abstract forms distinct from the people who are supposed to attain them: in particular their attitudes and aspirations, which can change over time. This study, informed by Legitimation Code Theory's (LCT) 'specialisation' concept (Maton 2014), surveyed student nurses (n = 310) in one UK university to find out what approach to learning they thought would lead to success in IT. The survey asked participants to select from four different 'specialisation' codes for four different subjects, and the responses were normalised. Each of the three year groups revealed a 'code shift', from a 'knowledge code' (ER+,SR-) in year 1, to a 'relativist code' (ER-,SR-) in year 2, to a 'knower code' (ER-,SR+) in year 3. The discussion offers some possible causes for these shifts and points to a possible contribution towards the field of digital literacies which has often depicted success in IT as a knowledge code, largely bypassing aspects of personality and intuition seen in the responses from year 3 students. Clearly further research would be needed to affirm and explicate these shifts.